1983
DOI: 10.1080/00223980.1983.9915391
|View full text |Cite
|
Sign up to set email alerts
|

Moral Judgment Maturity of Process and Reactive Schizophrenics

Abstract: Premorbid adjustment, paranoid symptomatology, and role orientation were examined as major predictors of moral judgment maturity in 40 male schizophrenics. In addition, control predictors included age, intelligence (block design and vocabulary), length of hospitalization, length of illness, social position (education and occupation), and severity of illness. A multiple regression equation of premorbid adjustment, block design and vocabulary combined, and education was the best predictor of moral judgment matur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2005
2005
2018
2018

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 8 publications
0
2
0
Order By: Relevance
“…The adolescents with schizophrenia were also rated by their teachers as displaying more delinquent behaviour than the controls. Herron, Stegen, Poland, and Schultz (1983) found that premorbid adjustment, block design scores (an index of nonverbal IQ) and vocabulary scores and years of education were the best predictors of moral maturity, assessed using the MJI, in a sample of 40 adult males with schizophrenia. Within this sample, only two participants focused on social systems and conscience, which Kohlberg argued that most healthy adults do.…”
Section: Previous Work On Moral Cognition In Schizophreniamentioning
confidence: 96%
See 1 more Smart Citation
“…The adolescents with schizophrenia were also rated by their teachers as displaying more delinquent behaviour than the controls. Herron, Stegen, Poland, and Schultz (1983) found that premorbid adjustment, block design scores (an index of nonverbal IQ) and vocabulary scores and years of education were the best predictors of moral maturity, assessed using the MJI, in a sample of 40 adult males with schizophrenia. Within this sample, only two participants focused on social systems and conscience, which Kohlberg argued that most healthy adults do.…”
Section: Previous Work On Moral Cognition In Schizophreniamentioning
confidence: 96%
“…Indeed, higher moral maturity scores on the MJI are related to higher mental age (Campagna & Harter, 1975), verbal intelligence (Harris et al, 1976) and abstract and analytic reasoning (Arbuthnot, 1973), including for people with schizophrenia (Herron et al, 1983). Interestingly, intelligence (IQ) may be more strongly predictive of moral maturity, as assessed using the MJI, for people of below average IQ than for those above average (Kohlberg, 1969).…”
Section: Previous Work On Moral Cognition In Schizophreniamentioning
confidence: 99%